Choice of Unmanipulated T Cell Replete Graft for Haploidentical Stem Cell Transplant and Posttransplant Cyclophosphamide in Hematologic Malignancies in Adults: Peripheral Blood or Bone Marrow—Review of Published Literature - Shatha Farhan; Edward Peres; Nalini Janakiraman (Advances in Hematology)
Allogeneic hematopoietic stem cell transplantation (SCT) is often the only curative option for many patients with malignant and benign hematological stem cell disorders. However, some issues are still of concern regarding finding a donor like shrinking family sizes in many societies, underrepresentation of the ethnic minorities in the registries, genetic variability for some races, and significant delays in obtaining stem cells after starting the search. So there is a considerable need to develop alternate donor stem cell sources. The rapid and near universal availability of the haploidentical donor is an advantage of the haploidentical SCT and an opportunity that is being explored currently in many centers especially using T cell replete graft and posttransplant cyclophosphamide. This is probably because it does not require expertise in graft manipulation and because of the lower costs. However, there are still lots of unanswered questions, like the effect of use of bone marrow versus peripheral blood as the source of stem cells on graft-versus-host disease, graft versus tumor, overall survival, immune reconstitution, and quality of life. Here we review the available publications on bone marrow and peripheral blood experience in the haploidentical SCT setting.